Long Noncoding RNA-Enriched Vesicles Secreted by Hypoxic Cardiomyocytes Drive Cardiac Fibrosis - Franziska Kenneweg; Claudia Bang; Ke Xiao; Chantal M. Boulanger; Xavier Loyer; Stephane Mazlan; Blanche Schroen; Steffie Hermans-Beijnsberger; Ariana Foinquinos; Marc N. Hirt; Thomas Eschenhagen; Sandra Funcke; et al. (Elsevier, 2019)
Long non-coding RNAs (lncRNAs) have potential as novel therapeutic targets in cardiovascular diseases, but detailed information about the intercellular lncRNA shuttling mechanisms in the heart is lacking. Here, we report an important novel crosstalk between cardiomyocytes and fibroblasts mediated by the transfer of lncRNA-enriched extracellular vesicles (EVs) in the context of cardiac ischemia. lncRNA profiling identified two hypoxia-sensitive lncRNAs: ENSMUST00000122745 was predominantly found in small EVs, whereas lncRNA Neat1 was enriched in large EVs in vitro and in vivo. Vesicles were taken up by fibroblasts, triggering expression of profibrotic genes. In addition, lncRNA Neat1 was transcriptionally regulated by P53 under basal conditions and by HIF2A during hypoxia. The function of Neat1 was further elucidated in vitro and in vivo. Silencing of Neat1 in vitro revealed that Neat1 was indispensable for fibroblast and cardiomyocyte survival and affected fibroblast functions (reduced migration capacity, stalled cell cycle, and decreased expression of fibrotic genes). Of translational importance, genetic loss of Neat1 in vivo resulted in an impaired heart function after myocardial infarction highlighting its translational relevance. Keywords: lncRNA, hypoxia, myocardial infarction, extracellular vesicles, Neat1